Implementasi Layanan Telepon dan SMS pada Jaringan Seluler Berbasis OpenBTS Dalam Situasi Bencana - Elvanno Hatorangan; Tutun Juhana (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2015)
When disasters occurs, cellular network might be down and cannot serve subscribers anymore. Meanwhile, many victims trapped in a wreckage might still have access to their mobile phone. An OpenBTS-based cellular network has been long before known as an ideal solution to rapidly deploy emergency GSM cellular network in situation after disaster. In this work, the methods which enable OpenBTS to assist the search for victims was developed. On the other hand, OpenBTS can also provide phone and SMS services so that victims can communicate with rescue teams who are conducting the search process. The voice and SMS services between victim’s mobile phone and SAR team’s smartphone were tested. As a result, phone service can be done by routing calls from victim’s cell phones in OpenBTS network to SAR team’s smartphone in wireless LAN networks. Thus, the SMS data from victim’s mobile phone can be stored in the database system. SMS data can then be accessed using a database browser.